Muslim Subjectivity in Soviet Russia The Memoirs of 'Abd al-Majid al-Qadiri - Bustanov, Alfrid; Usmanov, Vener (Brill, 2022)
The world as seen by a Qur'an specialist in late imperial and early Soviet Russia. Our book tells a dramatic story of 'Abd al-Majid al-Qadiri, a Muslim individual born in the Kazakh lands and brought up in the Sufi environment of the South Urals, who memorized the entire Qur'an at the Mosque of the Prophet. In Russia he travelled widely, performing the Qur'an recitations. The Stalinist terror was merciless to him: in total, he spent fifteen years of his life in labour camps in Solovki, in the North, and Tashkent, in the south. At the end of his life, al-Qadiri wrote the fascinating memoirs that we analysed and translated in this book for the first time. Al-Qadiri's life account allows us to look at the history of Islam in Russia from a new angle. His lively language provides access to everyday concerns of Russia's Muslims, their personal interactions, their emotions, and the material world that surrounded them. Al-Qadiri's book is a book of memory, full of personal drama and hope.